Anti-Inflammatory Effects of Curvularin-Type Metabolites from a Marine-Derived Fungal Strain Penicillium sp. SF-5859 in Lipopolysaccharide-Induced RAW264.7 Macrophages - Tran Minh Ha; Wonmin Ko; Seung Jun Lee; Youn-Chul Kim; Jae-Young Son; Jae Hak Sohn; Joung Han Yim; Hyuncheol Oh (Marine Drugs, 2017)
Chemical study on the extract of a marine-derived fungal strain Penicillium sp. SF-5859 yielded a new curvularin derivative (1), along with eight known curvularin-type polyketides (2–9). The structures of these metabolites (1–9) were established by comprehensive spectroscopic analyses, including 1D and 2D nuclear magnetic resonance (NMR) spectroscopy, and mass spectrometry (MS). In vitro anti-inflammatory effects of these metabolites were evaluated in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages. Among these metabolites, 3–9 were shown to strongly inhibit LPS-induced overproduction of nitric oxide (NO) and prostaglandin E2 (PGE2) with IC50 values ranging from 1.9 μM to 18.1 μM, and from 2.8 μM to 18.7 μM, respectively. In the further evaluation of signal pathways involved in these effects, the most active compound, (10E,15S)-10,11-dehydrocurvularin (8) attenuated the expression of inducible NO synthase (iNOS) and cyclooxygenase-2 (COX-2) in LPS-stimulated RAW264.7 macrophages. Furthermore, compound 8 was shown to suppress the upregulation of pro-inflammatory mediators and cytokines via the inhibition of the nuclear factor-κB (NF-κB) signaling pathway, but not through the mitogen-activated protein kinase (MAPK) pathway. Based on the comparisons of the different magnitude of the anti-inflammatory effects of these structurally-related metabolites, it was suggested that the opening of the 12-membered lactone ring in curvularin-type metabolites and blocking the phenol functionality led to the significant decrease in their anti-inflammatory activity.